ChemInform Abstract: Why Is Mannitol Becoming More and More Popular as a Pharmaceutical Excipient in Solid Dosage Forms?. Issue 48 (2nd December 2014) - Ohrem, H. Leonhard; Schornick, Eva; Kalivoda, Adela; Ognibene, Roberto
Abstract Review: 42 refs.